Réponses

2012-05-23T01:23:52+02:00

AB(xB-xA ; yB-yA)    AB(3-2 ;5-(-3))  AB(1 ; 8)

BC(xc-xb ; yc-yb)    BC(-1-3 ; -6-5)   BC(-4 ; -11)

CD ( xd-xc ; yd-yc)  CD(-2-(-1) ;0 -(-6)) CD(-1 ; 6)

AB + CD = (xAB + xCD ; yAB+yCD)  AB+CD( 1+(-1) ; 8+6)  AB+CD( 0 ; 14)

2AB+3BC=

  2AB=2( 1 ; 8) = ( 2 ; 16)

   3BC= 3(-4 ; -11) = (-12 ;-33)

 2AB+3BC=( 2 ; 16)+(-12 ;-33)  =( -12 ; -17)

2AB-3CD+4BC=

-3CD= -3(-1 ; 6) = ( 3 ; -18)

4BC= 4(-4 ; -11) = ( -16 ;-44)

2AB-3CD+4BC=( 2 ; 16)+( 3 ; -18)+( -16 ;-44) 

                     = ( -11 ; -46)